Study to Measure Impact of Product Packaging on Sales Enhancement - Dr. Kanika Garg, Ms. Umang; Ms. Kavita (International journal of economic perspectives, 2022)
The packaging plays an important role in regard to protect the product as well as in enhancing the sales. So, the present study measures the impact of product packaging on sales enhancement. In order to attain the objective the study selected 120 respondents as a sample who were the consumers. To achieve the objective regression model has been used. The study concludes that there is a positive impact of product packaging on sales enhancement.The study also conclude that product packaging influences sales enhancement by 26% in total. In the study of Wijayantiet.al (2018) also conducted a study to analyze the impact of product packaging design to increase sales and prove that packaging helps to gain profit.